A study on health and hygiene needs, strategies, and well‐being of an Aeta indigenous community in the Philippines through photovoice methods. Issue 3 (11th July 2020) - Yang, Eun‐Mi; Kim, Jwakyum; Biag, Al; Mangulabnan, Jefferson; Dela Cruz, Arlan; Sarmiento, Philip Joseph
Abstract: On a global scale, poor access to health and social welfare services for indigenous populations has threatened their overall well‐being, especially those living in remote or peripheral areas. Academics from two higher education institutions in South Korea and the Philippines conducted a community‐based research in an indigenous Aeta community in the highlands of Pampanga Province in the Philippines' Central Luzon region. Using a photovoice method and community survey, they investigated family health and hygiene as well as the current strategies this indigenous community employs to address their concerns. Results revealed that the community lacks the basic human needs and services such as water, food, shelter, education, and health service. They demonstrated, however, resilience in managing their lives by making use of the available natural resources and by drawing strength from community spirit. This study provided insights on how higher education institutions and other concerned agencies craft initiatives intended to benefit vulnerable populations and underserved communities such as the indigenous peoples.